2022
DOI: 10.3389/fnut.2022.840209
|View full text |Cite|
|
Sign up to set email alerts
|

The Interplay of Obesity, Dyslipidemia and Immune Dysfunction: A Brief Overview on Pathophysiology, Animal Models, and Nutritional Modulation

Abstract: Obesity has emerged as a leading global health concern. It is characterized by chronic low-grade inflammation, which impairs insulin signaling, lipid metabolism and immune function. Recent findings from animal and clinical studies have begun to elucidate the underlying mechanisms of immune dysfunction seen in the context of obesity. Here, we provide a brief review on the current understanding of the interplay between obesity, dyslipidemia and immunity. We also emphasize the advantages and shortcomings of numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 107 publications
0
9
0
1
Order By: Relevance
“…It can be merely calculated from the blood lipid levels, particularly triglycerides and HDL-C. It is an indirect indicator of visceral adiposity, and several studies have described the link between obesity, dyslipidemia, and adipose tissue dysfunction [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be merely calculated from the blood lipid levels, particularly triglycerides and HDL-C. It is an indirect indicator of visceral adiposity, and several studies have described the link between obesity, dyslipidemia, and adipose tissue dysfunction [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most significant contributing factor for obesity-related dyslipidemia is the increased free fatty acid release from adipose tissue to the liver. The enhanced free fatty acid release was proposed to lead to increased TG [ 8 ] and very-low-density lipoprotein (VLDL) production and can inhibit lipolysis, thereby promoting hypertriglyceridemia [ 9 ]. Moreover, lipolysis of triglycerides and LDL receptor expression is impaired in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Functional analysis of the gut microbiome across pregnant women at T2 revealed the significant enrichment of KOs involved in carbohydrate metabolism and immune-associated pathways. Previous findings have indicated that inflammation contributes to dyslipidemia in both the fasting and postprandial states 35 , reflecting the possibility that the gut microbiota may influence lipid profiles during pregnancy through inflammation.…”
Section: Discussionmentioning
confidence: 99%